Study of Mutual Effects of Neyshabur and Changsha Ceramics During the Abbasid Era (750- 1258 AD) - Moghanipoor, Majid Reza; Zafarmand, Seyed Javad; Rahmani, Ashkan (Journal of History Culture and Art Research, 2018)
Located in northeast of Iran, Neyshabur was one of the most prolific centers through the Abbasids (750 -1258 AD). The center was at its peak until the invasion of the Mongols (1258 AD) to Iran. Neyshabur’s location in the course of the Silk Road, made possible the especial opportunity of the west range of cultural inter- notation with other cultural centers. Hence the artifacts of Neyshabur were partly – mostly in technical and structural respect- inspired by the eastern civilizations, namely China, and on the other side in design and idea mostly depended on the Abbasid Khalifa-Emperor capitals. The present article is a comparative study of the mutual effects and interactions between Abbasid Neyshabur and Chinese ceramics, mostly produced in Changsha region, both at the eve of prolificacy, supposed that the Neyshabur products were directly inspired by the Changsha, one of the most developed centers for producing glazed ceramics. The study was formed on four major variables; form, technique, function and ornaments. The results of the study showed that there are major identical properties technique and function in both collection, and the most significant differences can be found in the types and high quality of the ornaments and decoration in Neyshabur products. Respectively, these types and styles of decoration especially in composition strategies for occupied and empty spaces in the designs of Changsha ceramics, were mostly inspired by the Neyshabur products. The results also showed that the differences could be refereed to different pictorial motifs and designs of the two regions, and attitudes of the producers, in other words, based on the defined aims, the Changsha ceramics were meant for mass production with definite commercial and economic intention in relation to other cultural centers. In contrast, the Neyshabur ceramics were intended for a more limited range of audience, which due to the more restricted variety of themes and decoration designs were produced for specific orders.